ANALISIS BEBAN KERJA MENTAL DENGAN METODA NASA-TASK LOAD INDEX - Simanjuntak, Risma Adelina (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2010)
C.V Pinus Bag’s Specialist runs for manufacture, especially in making many kinds of bags. By keeping quality of the products, it is the key to reach the goal of the company. This company applies production system of make to order which the orders have different model, numbers, and uncertain time cause mental workload was often felt by the workers. Therefore, it is studied by analyzing mental workload.In the study of men-tal workload, it was used the measurement of workload subjectively by using NASA-Task Load Index (TLX) method. This method is very effective for content 6 indicators (mental demand, physical demand, temporal demand ,performance, efforts, and frustration de-mand) with 16 employees of the company as respondents.The result that is obtained in this study shows that the mental workload NASA-TLX which is accepted by the employ-yees have been in high condition of workload. This can be seen based on the average of Weight Workload (WWL) with scale category; low category (0-9) is no employee, average category (10-29) is no employee, pretty high category (30-49 is no employee, high cate-gory (50-79) is 13 (thirteen) employees, very high category is 3 (three) employees. There-fore, the company needs to care optimal rest schedule to decrease work risk and re design of tasks and workplace in ergonomic.